Peran Lokus Pengendalian, Pengetahuan Keuangan, dengan Pendapatan sebagai Moderasi Terhadap Perilaku Manjemen Keuangan - Made Amanda Dewanti (Universitas Pendidikan Ganesha, 2022)
This study was conducted to determine the role of the locus of control, financial knowledge and income as moderation in influencing financial management behavior. The sample used in this study was 100 respondents from 7 official banjars in Sawan District, the age of the respondents used was from the age of 25 years to those aged > 50 years and had a livelihood as a private employee. The data analysis used in this study was SPSS. The findings of this study are that the locus of control and income have an influence on the formation of financial management behavior. This research can also prove that income cannot strengthen the influence between financial knowledge and financial management behavior. Some of the factors that cause this to happen, the first is lifestyle, the large number of family members that must be covered causes the salary generated cannot be set aside for saving or making investments Keywords: locus of control, financial knowledge, income, financial management behavior